2022
DOI: 10.31374/sjms.119
|View full text |Cite
|
Sign up to set email alerts
|

Øving på cybersikkerheit: Ein casestudie av ei cybersikkerheitsøving

Abstract: Denne artikkelen presenterer ein casestudie av ei cybersikkerheitsøving i militaer utdanning, og nyttar denne casestudien til å drøfte nokre utfordringar med cybersikkerheitsøvingar til utdanningsføremål. Casestudien gjer greie for sentrale avgjerder i designet av øvinga, evaluering av øvinga og utfordringar i øvingskonseptet. Gjennom ein litteraturgjennomgang samanliknar vi øvinga med liknande øvingar, og ser på korleis desse øvingane har blitt evaluert. Avslutningsvis nyttar vi casestudien og litteraturgjenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a previous study, we found that variations in daily affect were associated with experienced team workloads among cyber cadets participating in a cyber defense exercise (Ask et al, 2021b ). While the significance of such findings may be unclear with respect to exercise outcomes (Lund, 2022 ), the findings in the present study may serve to further elucidate their relevance beyond suggesting that individual characteristics influence team dynamics. While stress and urgency may disturb analytic cognitive processes (Poth, 2021 ), positive moods, as opposed to neutral moods may also result in transitioning from analytical processing to stimulus-oriented processing (Baek and Falk, 2018 ), for example as a result of optimism bias and mood congruent processing, lack of suspicion, or overconfidence (Vishwanath et al, 2018 ; Canham et al, 2022 ; Sütterlin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 70%
“…In a previous study, we found that variations in daily affect were associated with experienced team workloads among cyber cadets participating in a cyber defense exercise (Ask et al, 2021b ). While the significance of such findings may be unclear with respect to exercise outcomes (Lund, 2022 ), the findings in the present study may serve to further elucidate their relevance beyond suggesting that individual characteristics influence team dynamics. While stress and urgency may disturb analytic cognitive processes (Poth, 2021 ), positive moods, as opposed to neutral moods may also result in transitioning from analytical processing to stimulus-oriented processing (Baek and Falk, 2018 ), for example as a result of optimism bias and mood congruent processing, lack of suspicion, or overconfidence (Vishwanath et al, 2018 ; Canham et al, 2022 ; Sütterlin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 70%
“…In a previous study, we found that variations in daily affect was associated with experienced team workloads among cyber cadets participating in a cyber defense exercise (Ask et al, 2021b). While the significance of such findings may be unclear with respect to exercise outcomes (Lund, 2022), the findings in present study may serve to further elucidate their relevance beyond suggesting that individual characteristics influence team dynamics. While stress and urgency may disturb analytic cognitive processes (Poth, 2021), positive moods, as opposed to neutral moods may also result in transitioning from analytical processing to stimulus-oriented processing (Baek & Falk, 2018), for example as a result of optimism bias and mood congruent processing, lack of suspicion, or overconfidence (Canham et al, 2022;Sütterlin et al, 2022;Vishwanath et al, 2016).…”
Section: Discussionmentioning
confidence: 53%